Karakteristik Briket Pelepah Kelapa Sawit Menggunakan Metode Pirolisis Dengan Perekat Tepung Tapioka - Dani Saputra; Ahdiat Leksi Siregar; Istianto Budhi Rahardja (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
The energy crisis in Indonesia is marked by the increasing scarcity of fuel oil in the midst of society. One of the alternative energy sources is charcoal briquettes, where the ingredients are derived from solid waste from palm fronds. This study aims to determine the characteristics of oil palm midrib briquettes with 50% tapioca flour adhesive. The palm fronds were chopped to a size of ± 5 cm and then put into the pyrolysis chamber. Oil palm fronds were burned with a little oxygen at a temperature of 200-300⁰C for 3 hours. The result of pyrolysis combustion from oil palm fronds in the form of charcoal, then ground and filtered with a mesh of 60. The charcoal is glued with tapioca flour in a ratio of 2:1. Briquette testing is carried out at the Briquette Testing Laboratory provider to determine the parameters of combustion time, calorific value, moisture content, ash content, and carbon content that occur. From the test results, the following parameters are obtained: the average burning time is 1 minute/gr, the calorific value is 5.361kcal/kg wet basis and 5.863 kcal/kg dry basis, the water content is 8.56%, the ash content is 6.84 % wet basis and 7.48% dry basis, volatile matter is 36.96% wet basis and 40.42% dry basis and fixed carbon 47.64% wet basis and 52.10% dry basis.